2004
DOI: 10.1002/aoc.617
|View full text |Cite
|
Sign up to set email alerts
|

Re‐evaluation of distillation and comparison with HNO3 leaching/solvent extraction for isolation of methylmercury compounds from sediment/soil samples

Abstract: Distillation was re-evaluated for the formation of artifacts arising from increasing naturally occurring mercury(II) concentrations, as opposed to previous identification of artifacts by spiking standard mercury(II) into samples. Naturally occurring mercury(II) concentrations lower than 2 µg g −1 were found not to affect methylmercury (MeHg) results. However, when the natural concentrations of mercury(II) were greater than 2 µg g −1 , in contrast to standard mercury(II) spiked in samples, the MeHg concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(36 citation statements)
references
References 13 publications
1
34
1
Order By: Relevance
“…For Hg analysis, soil samples were first digested with HNO 3 + HCl (10 ml, 1:1 v/v) in a teflon tube at 100°C for 2 h. Total Hg concentration was then determined using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Soil samples were prepared for MeHg analysis using CuSO 4 -methanol/solvent extraction according to the method outlined by (Liang et al 2004), following which MeHg contents were determined using HPLC-ICP-MS.…”
Section: Chemical Analysismentioning
confidence: 99%
“…For Hg analysis, soil samples were first digested with HNO 3 + HCl (10 ml, 1:1 v/v) in a teflon tube at 100°C for 2 h. Total Hg concentration was then determined using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Soil samples were prepared for MeHg analysis using CuSO 4 -methanol/solvent extraction according to the method outlined by (Liang et al 2004), following which MeHg contents were determined using HPLC-ICP-MS.…”
Section: Chemical Analysismentioning
confidence: 99%
“…Three rice paddies were selected in Guizhou province, southwestern China, including the background site (located at the Guizhou Rice Research Institute) and the moderately-and highly-contaminated sites (both located (Liang et al, 1996(Liang et al, , 2004, then MeHg was quantified using the same methods described for pore water MeHg concentrations following EPA Method 1630.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure of Hintelmann et al [5,11] was used for sample preparation (distillation), followed by aqueous-phase ethylation (derivatization) and detection (GC-ICP-MS), according to the P1 procedure shown in Figure 1 (steps 3-5). During MeHg analysis, special attention was paid to sample aliquots to be distilled to maintain the original species distribution and avoid species transformation (formation of MeHg artifacts [10,17,19]); aliquots containing 1 to 2 g sediment (MeHg fraction 0.28%) were taken for distillation. The results were used as a method of comparison for isotopically enriched MeHg quantification, as well as for total methylmercury (SMeHg-all isotopes) values.…”
Section: Reagentsmentioning
confidence: 99%
“…Using an acid extracting procedure (HNO 3 leaching), Liang et al [17] observed no artifact formation, and noted that the measured MeHg was independent of the naturally occurring Hg(II) content in the aliquots of the analyzed sediment samples. In our tests, the stable isotope spike ( 200 Hg 2þ ) and the internal standard (Me 201 Hg) were added just before the acid KBr-CuSO 4 mixture, and no additional MeHg formation was noticed (Table 3) for all samples, except F4 for which a small increase was measured.…”
Section: Formation Of Mehg Artifactsmentioning
confidence: 99%
See 1 more Smart Citation